Appropriateness of Empirical Prescriptions of Ceftriaxone and Identification of Opportunities for Stewardship Interventions: A Single-Centre Cross-Sectional Study - Ana Gorgulho; Flávia Cunha; Elsa Alves Branco; Ana Azevedo; Francisco Almeida; Raquel Duro; Paulo Andrade; Nuno Rocha Pereira; Carlos Lima Alves (MDPI AG, 2023)
Third-generation cephalosporins are widely used due to the convenient spectrum of activity, safety, and posology. However, they are associated with the emergence of multidrug-resistant organisms, which makes them important targets for antimicrobial stewardship interventions. We aimed to assess the appropriateness of empirical prescriptions of ceftriaxone in a tertiary hospital. This cross-sectional study analysed empirical ceftriaxone prescriptions in January and June 2021. Patients under other antimicrobials 48 h before admission were excluded. The quality of ceftriaxone prescription was assessed regarding the initial appropriateness, duration of inappropriate ceftriaxone therapy, and missed opportunities for de-escalation. Of 465 prescriptions, 46.5% were inappropriate. The ceftriaxone prescription was inappropriate in 95.7% of lower respiratory tract infections (LRTI) globally and in nearly 40% of urinary tract infections (UTI) in medical and intensive care departments. Intensive care, internal medicine, and palliative care departments showed the highest number of inappropriate ceftriaxone prescriptions and longer length of inappropriate ceftriaxone prescriptions compared to the hospital's average. Improvement of empirical ceftriaxone prescription in LRTI and urinary infections, adherence to local guidelines and de-escalation practices, and targeted interventions focusing on critical departments may significantly reduce the inappropriate empirical use of ceftriaxone.